Bot to Monitor Student Activities On E-Learning System Based On Robotic Process Automation (RPA) - Munawar, Ghifari (Sinkron : jurnal dan penelitian teknik informatika, 2021)
Student activities in the e-learning system need to be monitored regularly by lecturers to observe their learning achievements. The monitoring process carried out is monitoring student attendance, collecting assignments, and taking quizzes. This will be a burden if it is done regularly, especially if the lecturer teaches many subjects. Robotic process automation (RPA) is a technology that uses software agents (bots) to imitate human work processes to be automated. The objectives of this research are (1) applying RPA technology as bots that can monitor student activity on the e-learning system (Moodle), and (2) measuring the time efficiency of RPA bots in processing their work. The research stages are divided into three, namely: the preparation stage, the RPA implementation stage, and the evaluation stage. The preparation stage is carried out to define the problem to be handled, the RPA implementation stage to develop bots using the UiPath platform, and the evaluation stage to compare the efficiency of work time between bots and manually (by humans). The RPA bot was developed on four work focuses, namely (1) attendance monitoring, (2) task collection monitoring, (3) quiz processing monitoring, and (4) email delivery automation. Efficiency testing was carried out on four test scenarios (FR1, FR2, FR3, FR4), where FR2 had the highest percentage of work time efficiency at 754%, and the lowest was in FR1 with a percentage of 165%, with an overall average efficiency percentage of 444%. Thus, through RPA technology, monitoring work becomes faster and saves effort.